2017
DOI: 10.1007/5584_2017_14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Socioeconomic Factors on Self-Reported Prevalence of Allergic Diseases Among Female University Students

Abstract: Until recently, most studies report an increasing prevalence of allergy and asthma. The research suggests that the increase may have to do with changes in lifestyle and living conditions. This study seeks to determine the prevalence and changes in allergic diseases in relation to socioeconomic status (SES) 6 years apart. The research material consisted of data collected in two cross-sectional surveys conducted among university female students in 2009 and 2015 (respectively, 702 and 1305 subjects). The surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
1
6
0
2
Order By: Relevance
“…Allergy is a widespread global public health problem 1. It has continuously escalating rates, and it can lead to serious complications 1,2. The etiology of allergy is due to interactions between both environmental factors, with the permissive genetic factors 3.…”
Section: Introductionmentioning
confidence: 99%
“…Allergy is a widespread global public health problem 1. It has continuously escalating rates, and it can lead to serious complications 1,2. The etiology of allergy is due to interactions between both environmental factors, with the permissive genetic factors 3.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis within this population showed that chronic STH infections were associated with a generalized suppression of mitogen‐induced type 1 and type 2 cytokines, probably explained by enhanced production of spontaneous IL‐10 . Thus, changes in immune regulation within populations that are related to improvements in sanitary conditions may contribute to an increased prevalence of allergic diseases observed over recent decades in low‐ and middle‐income countries such as Brazil …”
Section: Impact Of Sanitation On Prevalence Of Parasitic Infections Amentioning
confidence: 89%
“…Brazil. [40][41][42] An inverse correlation between the prevalence of helminth parasitic infections and asthma can be seen regionally within Brazil between areas with different sanitary and socio-economic conditions:…”
Section: Ascaris Lumbricoides Hookwormmentioning
confidence: 99%
“…Provavelmente dois fatores poderiam explicar estas diferenças. Uma é que em Ijuí os escolares são de nível socioeconômico mais elevado (52,8% vs. 18,3% -Porto Alegre) e há literatura consistente que indica que quanto melhor é essa situação, maior o índice de doenças alérgicas [10,23]. Outro aspecto importante são as características regionais, sendo Ijuí uma região agrícola, é exposta a contaminação ambiental resultante do manejo de diferentes plantações, o que pode elevar a prevalência de sintomas de doenças alérgicas.…”
Section: Discussionunclassified
“…A asma tem características multicausais e sua manifestação apresenta relação com as condições ambientais, geográficas, socioeconômicas, emocionais e genéticas. Além disso, estudos descrevem diferenças para manifestação e intensidade dos sintomas de asma entre regiões urbanas e rurais [7][8][9][10][11].…”
Section: Introductionunclassified